Determinant of Household Food Waste: A Direct Measurement Study in Tanah Sareal Sub-District of Bogor City - Rahmaniya, Liya Putri; Briawan, Dodik; Sukandar, Dadang; Swamilaksita, Prita Dhyani (Media Gizi Indonesia, 2025)
The percentage of food waste generation has increased in Indonesia for 20 years, with 80% of food waste coming from households. This can cause various significant negative impacts on the environment, economy and social. Various factors affect the production of household food waste. This study aims to analyze household food waste based on its quantity, type, and determinants. This study uses some secondary data from primary research conducted by Swamilaksita (2024) with a cross-sectional design. The study sample of 110 households was selected using a stratified random sampling technique. Food waste data was obtained through direct measurement using the SNI 19-3964-1994 method. The entire data was analyzed descriptively, while multiple linear regression analysis was carried out to determine the determinants of household food waste. This study showed that the average amount of food waste was 318.4 g/HH/day and 76.7 g/cap/day. The cereal group was the most discarded food group, followed by vegetables and fruits group. Only three variables were proven to be statistically significant (p-value<0.1) affect the average amount of household food waste, namely the number of household members (p=0.000), mother work as civil servant/private employee (p=0.049), and purchasing and spending behavior (p=0.084). The conclusion was there is an average amount of food waste in units per household and per capita, with the dominant food group is the cereal group, as well as the determinants of household food waste, including number of household members, mother work as a civil servant/private employee, and purchasing and spending behavior.